The impact of diabetes mellitus on tendon pathology: a review - Xu, Jian; Wang, Jinbo; Ji, Yuncong; Liu, Yanlong; Jiang, Jishi; Wang, Yanbo; Cui, Xilong; Wan, Yunpeng; Guo, Biao; Yu, Haiyang (Frontiers in Pharmacology, 2024)
Diabetes is one of the most common metabolic diseases worldwide, leading to complications, mortality, and significant healthcare expenditures, which impose a substantial social and financial burden globally. A diabetic environment can induce metabolic changes, negatively affecting tendon homeostasis, leading to alterations in biomechanical properties and histopathology. Numerous studies have investigated the mechanisms through which diabetes exerts pathological effects on tendons, including increased free radical production, oxidative stress, inflammatory responses, deposition of advanced glycation end products (AGEs), and microvascular changes. These metabolic changes damages tendon structure, biomechanics, and tendon repair processes. The proliferation of tendon stem cells decreases, apoptosis increases, and abnormal differentiation, along with abnormal expression of myofibroblasts, ultimately lead to insufficient tendon repair, fibrosis, and remodeling. Although researches unveiling the effects of diabetes on tendinopathy, fibrosis or contracture, and tendon injury healing are growing, systematic understanding is still lacking. Therefore, this review summarizes the current research status and provides a comprehensive overview, offering theoretical guidance for future in-depth exploration of the impact of diabetes on tendons and the development of treatments for diabetes-related tendon diseases.